IMPLEMENTASI MEDIA GAME MUROJA’AH DALAM MENINGKATKAN HASIL BELAJAR TAHFIDZ AL-QUR’AN SISWA SMP IT NUR HIKMAH - Barqasyami, Ahmad; Fauziyah, Nur Laily; Hidayatullah, M. Agung (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Complaints about the difficulty of memorizing the verses of the Koran among children do not only belong to the children of clerics, children of ustadz or children of doctors, However, it has become a common phenomenon, even in educational institutions, memorization is a frightening threat, sometimes children become bored and stressed. One alternative way that can help revive children's enthusiasm for memorizing and repeating the Koran by heart is the muroja'ah game. This research aims to determine the application of the muroja'ah game as an alternative way to overcome children's boredom in memorizing verses of the Quran. The second objective is to determine whether or not there is an increase in the learning outcomes of tahfidz al-Quran by using the muroja'ah game. The method used in this research is a quantitative experimental method. In collecting data, through primary sources, namely observation, interviews and tests. Data analysis in this research is paired sample t-test analysis. The results of the research show that the application of the murojaah game media is able to train students' memory and help students more easily remember verses that are difficult to memorize, and able to help students remember verse numbers with the question instruments contained in the three parts of the test in the muroja’ah game media. Statistical data shows an increase in students' tahfidz results, namely before implementing the muroja’ah game with a mean value of 74.40 to 82.44 after implementing the murojaah game media.